2011
DOI: 10.1371/journal.ppat.1002398
|View full text |Cite
|
Sign up to set email alerts
|

Acid Stability of the Hemagglutinin Protein Regulates H5N1 Influenza Virus Pathogenicity

Abstract: Highly pathogenic avian influenza viruses of the H5N1 subtype continue to threaten agriculture and human health. Here, we use biochemistry and x-ray crystallography to reveal how amino-acid variations in the hemagglutinin (HA) protein contribute to the pathogenicity of H5N1 influenza virus in chickens. HA proteins from highly pathogenic (HP) A/chicken/Hong Kong/YU562/2001 and moderately pathogenic (MP) A/goose/Hong Kong/437-10/1999 isolates of H5N1 were found to be expressed and cleaved in similar amounts, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
157
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(165 citation statements)
references
References 45 publications
8
157
0
Order By: Relevance
“…Relatively unstable HA proteins from HPAI viruses are protected from inactivation while trafficking through the secretory pathway by M2 ion channel activity, which neutralizes the mildly acidic trans-Golgi compartment (19). In avian-like H5N1 viruses, relatively high HA activation pH values (5.6-6.0) were associated with greater growth and pathogenicity in chickens (20,21) and greater growth and transmission in mallard ducks (22). A stabilizing mutation that reduced H5N1 HA activation pH from 5.9 to 5.4 attenuated growth and eliminated transmission in ducks but enhanced growth in the upper (but not lower) respiratory tracts of mice and ferrets (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively unstable HA proteins from HPAI viruses are protected from inactivation while trafficking through the secretory pathway by M2 ion channel activity, which neutralizes the mildly acidic trans-Golgi compartment (19). In avian-like H5N1 viruses, relatively high HA activation pH values (5.6-6.0) were associated with greater growth and pathogenicity in chickens (20,21) and greater growth and transmission in mallard ducks (22). A stabilizing mutation that reduced H5N1 HA activation pH from 5.9 to 5.4 attenuated growth and eliminated transmission in ducks but enhanced growth in the upper (but not lower) respiratory tracts of mice and ferrets (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…An unstable HA protein is more prone to inactivation, whereas a very stable HA is more susceptible to lysosomal degradation. A higher HA activation pH (5.6-6.0) enhances replication of HPAI viruses in the enteric and respiratory tracts of ducks and chickens by facilitating membrane fusion (20,22). Such facile activation of the HA protein leads to virion inactivation in mildly acidic pH environments, such as the mammalian upper respiratory tract (7,8,23,25).…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising given that the 110-helix found in VE is involved in the interaction between HA1 and the loop B of HA2 which undergoes a loop-to-helix transition upon protonation at low pH [17]. For example, several residues in HA were found to be responsible for difference in pathogenicity of two H5N1 isolates, namely a HPIAV strain (A/chicken/Hong Kong/YU562/2001) and a moderately pathogenic strain (A/goose/Hong Kong/437-10/1999), and two of these residues are found in the VE subdomain [39,40]. It was further shown that the pH stability of HA protein is correlated with the pathogenesis of H5N1 virus and the higher activation pH in the HPIAV is mainly due to mutations N104D and T115I which are located at the N-and C-termini of the 110-helix respectively [40].…”
Section: In Vivo Studies Of Ve Binding Mabsmentioning
confidence: 99%
“…For example, several residues in HA were found to be responsible for difference in pathogenicity of two H5N1 isolates, namely a HPIAV strain (A/chicken/Hong Kong/YU562/2001) and a moderately pathogenic strain (A/goose/Hong Kong/437-10/1999), and two of these residues are found in the VE subdomain [39,40]. It was further shown that the pH stability of HA protein is correlated with the pathogenesis of H5N1 virus and the higher activation pH in the HPIAV is mainly due to mutations N104D and T115I which are located at the N-and C-termini of the 110-helix respectively [40]. These mutations are hypothesised to affect the stability of the 110-helix and its interaction with HA2, thus resulting in higher sensitivity to pH-induced conformational change.…”
Section: In Vivo Studies Of Ve Binding Mabsmentioning
confidence: 99%
“…The mutations related to this change were identified in various HA regions, including the receptor-binding domain [36], interface between the HA1 and HA2 subunits [37][38][39], the coiledcoil regions of the HA2 subunit [37,40,41], and the fusion peptide pocket [40,42]. However, it seems that passages in eggs impair the virus stability less dramatically than the analogous passages in both cell lines.…”
Section: Virus Adaptation Passages and Their Consequencesmentioning
confidence: 99%